Frailty and Health-Related Quality of Life Among Residents of Long-Term Care Facilities. (August 2013) - Kanwar, Amrit; Singh, Mandeep; Lennon, Ryan; Ghanta, Kalyan; McNallan, Sheila M.; Roger, Véronique L.
Objectives: To determine the prevalence and relationship of frailty and health-related quality of life (HRQOL) among residents of long-term care [nursing homes (NH) and assisted living (AL)] facilities.Methods: Residents of NH and AL facilities in La Crosse County, Wisconsin, were recruited 1/2009-6/2010 and assessed for frailty (gait speed, unintended weight loss, grip strength), comorbidity (Charlson index), and HRQOL [Short Form (SF)-36].Results: Among 137 participants, 85% were frail. Frail residents were older, had more comorbidities (2.0 vs. 0, p < .001) and lower mean SF-36 Physical Component Score (PCS, 32 vs. 48, p < .001). Following adjustments for age, sex, and comorbidities, compared to nonfrail residents, frail residents had lower SF-36 PCS (mean difference −14.7, 95% CI. −19.3, −10.1, p < .001). Frailty, comorbidity, and HRQOL did not differ between NH and AL facilities.Discussion: Frail residents had lower HRQOL, suggesting that preventing frailty may lead to better HRQOL among residents of long-term care facilities.